2015
DOI: 10.1128/jvi.02070-15
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Directed toward the Hepatitis C Virus Glycoprotein E2 Detect Antigenic Differences Modulated by the N-Terminal Hypervariable Region 1 (HVR1), HVR2, and Intergenotypic Variable Region

Abstract: Hepatitis C virus (HCV) envelope glycoproteins E1 and E2 form a heterodimer and mediate receptor interactions and viral fusion. Both E1 and E2 are targets of the neutralizing antibody (NAb) response and are candidates for the production of vaccines that generate humoral immunity. Previous studies demonstrated that N-terminal hypervariable region 1 (HVR1) can modulate the neutralization potential of monoclonal antibodies (MAbs), but no information is available on the influence of HVR2 or the intergenotypic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 43 publications
4
83
0
Order By: Relevance
“…Our analysis clearly demonstrated that simultaneous replacement of HVR2 and the igVR cooperatively stabilized the CD81-binding site within E2, despite these individual mutations resulting in reduced CD81-LEL binding. We have recently reported that the ability of both a neutralizing antibody and an apparently nonneutralizing antibody to inhibit E2-CD81 binding was significantly improved when HVR2 and the igVR were deleted, with or without HVR1, suggesting that these variable regions can modulate the CD81-LEL binding site and epitopes therein (52).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis clearly demonstrated that simultaneous replacement of HVR2 and the igVR cooperatively stabilized the CD81-binding site within E2, despite these individual mutations resulting in reduced CD81-LEL binding. We have recently reported that the ability of both a neutralizing antibody and an apparently nonneutralizing antibody to inhibit E2-CD81 binding was significantly improved when HVR2 and the igVR were deleted, with or without HVR1, suggesting that these variable regions can modulate the CD81-LEL binding site and epitopes therein (52).…”
Section: Discussionmentioning
confidence: 99%
“…7), HVR2 from one E2 monomer is positioned close to HVR1 from another monomer and is flanked on another side by IgVR. This observation is supported by experimental data suggesting that HVR1, HVR2, and IgVR are structurally linked in the virion (64). For example, antibodies that bind epitope I in E2 have been shown to exhibit improved binding to E2 and an improved ability to inhibit E2-CD81 interactions when any one of these hypervariable regions was deleted.…”
Section: Figmentioning
confidence: 61%
“…For example, antibodies that bind epitope I in E2 have been shown to exhibit improved binding to E2 and an improved ability to inhibit E2-CD81 interactions when any one of these hypervariable regions was deleted. Furthermore, inhibition of the E2-CD81 interaction was additive if two or more of the hypervariable regions were deleted (64). In addition, antibodies that recognize an epitope that included HVR1 residues were shown to have a reduced affinity for E1/E2 when IgVR was deleted but not when IgVR and HVR2 were deleted simultaneously (64).…”
Section: Figmentioning
confidence: 98%
See 2 more Smart Citations